IMPLEMENTASI PENGEMBANGAN MUATAN KURIKULUM BERBASIS KEARIFAN LOKAL MANGGARAI DI PAUD BUNDA MARIA GRAZIA - De Gomes, Fransiskus; Sidi, Yasinta (NANAEKE: Indonesian Journal of Early Childhood Education, 2022)
Stimulation of early childhood development should be based on local wisdom of children's culture to build the basis for their behavior. For this reason, the Early Childhood Education Unit needs to develop a curriculum based on local wisdom as the basis for implementation in stimulating children's development. This study aims to describe the implementation of the development of curriculum content based on Manggarai local wisdom in PAUD Bunda Maria Grazia in Langke Rembong District. This study uses a qualitative descriptive research method. The subjects of this study were the principal, teachers who numbered 2 people. Data collection techniques in this study use observation, interviews, and documentation. The validity test of the researcher data is using technical triangulation technique. Data analysis used in this research is qualitative data analysis of the Miles and Huberman models. The results showed that first, the implementation of local content in learning in PAUD Bunda Maria Grazia was the development of simple local content values. This means that the values of local content developed are the values of local content that are close to children's lives, for example about local customs, traditional houses, regional dances. Second, the implementation of local content values in the learning process is developed based on the themes and sub-themes that already exist. The teacher developed the theme of sports and cultural arts into several sub-themes that have cultural elements, including sub-themes of lawo agu meong playing, sub-themes of rangkuk alu dance, ndundu dake music, painting and drawing of mbaru gendang. The sub-themes were developed into a range of material covering types, names, characteristics, and ways of the lawo agu meong role playing, dancing the rangkuk alu, dancing the ndundu dake, painting and drawing mbaru gendang. The results of this study conclude that: first, local content values ​​developed by schools are more of cultural values, while regional characteristics and potentials have not been developed and integrated into the learning process. Second, the implementation model for developing local content values ​​at PAUD Bunda Maria Grazia is an introduction to simple local content values ​​that are close to children's lives or what children encounter on a daily basis.